2013
DOI: 10.4103/0970-9290.127623
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alveolar bone thickness due to retraction of anterior teeth during orthodontic treatment: A cephalometric and computed tomography comparative study

Abstract: When incisors are retracted, the risk of adverse effect is present. This must be carefully monitored to avoid negative iatrogenic effects. This study needs follow up after 6 months or 1 year after completion of the orthodontic treatment to assess the long-term consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…All five articles were retrospective, and of moderate quality according to the criteria proposed by Mattos et al (9). Four concerned Angle class I patients with double protrusion who underwent extraction of the four first premolars (6,13,14,15), while the remaining work studied class II division 1 patients who underwent extraction of the maxillary first premolars (3) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All five articles were retrospective, and of moderate quality according to the criteria proposed by Mattos et al (9). Four concerned Angle class I patients with double protrusion who underwent extraction of the four first premolars (6,13,14,15), while the remaining work studied class II division 1 patients who underwent extraction of the maxillary first premolars (3) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies had been approved by an ethics committee (13-15). The other two articles did not mention approval (3,6).…”
Section: Resultsmentioning
confidence: 99%
“…As our objective was to assess changes in alveolar bone thickness from buccal to palatal cortical bone, this distance was measured in a standardized and reproducible manner. We did not measure the distances from the tooth root to the buccal cortical bone and from the tooth root to the palatal cortical bone as other authors did, 2 , 24 since this measure reflects mainly the displacement of the tooth root through the alveolar bone and not specifically changes in bone thickness of the region of interest. Our study presented small non-significant differences in alveolar bone thickness, which either decreased or increased.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also suggested that there were limitations in the amount of incisor retraction in patients with a very thin anterior cortical plate in the maxilla, thus in patients with severe skeletal discrepancies, orthognathic surgery should be considered 13 . Also, the studies on the labial and palatal alveolar bone thickness of incisors after incisor retraction showed more significant changes in palatal bone compared to the labial side 4,5,10 .…”
mentioning
confidence: 94%
“…However, if there is excessive lingual inclination of anterior teeth as a result of putting too much emphasis on the esthetic aspect without considering the alveolar bone remodeling response following orthodontic tooth movement, unwanted iatrogenic sequelae such as root resorption, alveolar bone loss and fenestration, dehiscence and gingival recession would likely occur 4 10 .…”
Section: Introductionmentioning
confidence: 99%